Mobile AR Beauty Filter: The Mediating Role of App/Brand Congruence between Customer Inspiration and Experience Extension in Indonesia - Cantika Putri Morellia; Febzi Fiona (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study examines the mediating role of app/brand congruence in the relationship between customer inspiration and experience extension in the context of a leading cosmetics brand AR beauty filter usage on TikTok in Indonesia. Research Design & Methods: Adopting the S-O-R Theory and Technology Acceptance Model, this study tests the influence of augmentation quality, AR expertise, and app ease of use on customer inspiration, and its impact on experience extension and purchase intention. A quantitative survey approach was employed, collecting data from 430 active users of the brand’s AR beauty filters via purposive sampling. PLS-SEM analysis was conducted using SmartPLS 4, incorporating education and fashion shopping interest as control variables. Findings: Augmentation quality is the strongest determinant of customer inspiration, followed by AR expertise and app ease of use. Customer inspiration directly drives experience extension and also operates through app/brand congruence as a partial mediating. Customer inspiration is the strongest predictor of purchase intention in the model. Education significantly influences purchase intention, whereas fashion shopping interest does not significantly effect either outcome variable. Implications & Recommendations: Brands should prioritize augmentation quality, ease of use, and brand-filter congruence in AR filter design to maximise consumer inspiration leading to experience extension and purchase intention. Marketing communication strategies should be differentiated based on consumer education levels. Contribution & Value Added: This study extends AR marketing literature by establishing app/brand congruence as a partial mediating in a social media integrated AR context, distinguishing it from prior findings of full mediation in standalone AR applications.